The behaviour of positron clouds in the single-particle regime under the influence of rotating wall electric fields - Michael Charlton (New Journal of Physics, 2012)
Positron clouds are compressed following accumulation in a Surkotype two-stage buffer gas trap using an asymmetric rotating wall electric field. An analytic theory used to describe measurements of the rate of compression is discussed. Furthermore, we describe measurements taken without the rotating wall applied and with the rotating wall compression present during accumulation of the positron cloud. This has enabled total loss rates for the positrons via annihilation and collisional-induced radial transport to be isolated, with the latter mechanism found to be dominant. We have shown that the application of the rotating wall at a resonant frequency virtually eliminates radial transport, such that the positron loss is caused by annihilation in the gas.